An exploratory study of goods and services tax awareness in Malaysia - L., Saira; M.A., Zariyawati; L., Yoke-May (Institute of Tun Dr. Mahathir Mohamad’s Thoughts, Universiti Utara Malaysia Sintok, 2010)
Tax has been recognized as one of the main sources of governments’ income. Goods and Services Tax (GST) is an example of tax that contributes to the governments’ income. This tax has been implemented in many countries such as Canada, Australia and New Zealand. GST is a tax imposed on the sale of goods and services. In recent years, this issue on GST has been raised by the Malaysian Government as an approach to reduce its deficit. However, the Malaysian Government is still finding the right time to implement GST as they are still conducting studies on the social impact of GST. This study attempts to investigate Malaysian awareness towards the upcoming of GST implementation.